2021
DOI: 10.1002/jts.22662
|View full text |Cite
|
Sign up to set email alerts
|

Treating Veterans at Risk for Suicide: An Examination of the Safety, Tolerability, and Outcomes of Cognitive Processing Therapy

Abstract: Individuals with posttraumatic stress disorder (PTSD) are at increased risk for suicidal thoughts and behaviors; however, clinicians often report apprehension about recommending trauma‐focused therapy to patients with an increased risk of suicide. The present study aimed to evaluate the safety, tolerability, and response to cognitive processing therapy (CPT) among a sample of military veterans with PTSD and increased suicide risk. A secondary aim was to provide a clinically useful definition of high suicide ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…There were 11 studies that included CPT. Eight studies examined CPT only (Blain et al., 2020; Bryan et al., 2018; Resick et al., 2017; Stayton et al., 2019; Johnson et al., in press; Holliday et al., 2018; Horwitz et al., 2018; Roberge et al., 2021) and three studies compared CPT to another EBT (Bryan et al., 2016; Gradus et al., 2013; Post et al., in press; Resick et al., 2015). Ten CPT studies showed reductions in both PTSD‐ and suicide‐related outcomes, with the majority reporting significant reductions and, generally, few or no reports of suicidal ideation or behaviors at posttreatment or follow‐up assessments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 11 studies that included CPT. Eight studies examined CPT only (Blain et al., 2020; Bryan et al., 2018; Resick et al., 2017; Stayton et al., 2019; Johnson et al., in press; Holliday et al., 2018; Horwitz et al., 2018; Roberge et al., 2021) and three studies compared CPT to another EBT (Bryan et al., 2016; Gradus et al., 2013; Post et al., in press; Resick et al., 2015). Ten CPT studies showed reductions in both PTSD‐ and suicide‐related outcomes, with the majority reporting significant reductions and, generally, few or no reports of suicidal ideation or behaviors at posttreatment or follow‐up assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Ten CPT studies showed reductions in both PTSD‐ and suicide‐related outcomes, with the majority reporting significant reductions and, generally, few or no reports of suicidal ideation or behaviors at posttreatment or follow‐up assessments. Although one study reported suicide attempts by two participants approximately 7 months following treatment and one suicide attempt from a participant who completed just one session (i.e., combined 1% of the sample), the results showed that CPT significantly reduced PTSD symptoms regardless of patients’ baseline level of suicide risk (Roberge et al., 2021). For all studies that compared CPT to other EBTs, both EBTs resulted in improvement in PTSD and suicide outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Undoubtedly, these associations are multidirectional and intertwined, but targeting the most impaired dimension may reduce suicide risk most effectively. Finally, although suicide risk has been used as an exclusionary criterion for PTSD treatment, emerging research suggests that both conditions can safely be treated concurrently (Roberge et al., 2021; Rozek et al., in press). This means that clinicians are able to target the most impaired domain of functioning across both conditions (i.e., PTSD and suicide), more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Roberge and colleagues (2021) dug even more deeply into the question of whether CPT is safe, tolerable, and effective for treating traumatized veterans with both PTSD and suicidal risk. Using a chart review of 290 veterans who participated in CPT at a Veteran's Affairs hospital, the investigators found that over half of the participants reported risk of suicide at intake, as measured by a history of previous suicide attempts or current suicidal ideation.…”
mentioning
confidence: 99%